The cross of Motupe: Regional pilgrimage center in northern Peru - Van Ronzelen de González, Teresa (1988)
The pilgrimage to the Holy Cross of Motupe (or Chalpón) is, in our opinion, the most important on the north coast of the country. The town of Motupe, located just over 80 kilometers to the north of the city of Chiclayo (capital of the Department of Lambayeque), is the scene, in August, of the largest demonstration in the Popular Region of northern Peru. Motupe, a town of 18,000 inhabitants, is host to more than two hundred thousand pilgrims who, for 2 weeks, come mostly from the entire northern coast of the country, Cajamarca and Lima (mostly migrants) to worship the Motupe Cross.